Teaching "Quanti" – Lessons from French Experiences in Sociology and History. Issue 1 (October 2017) - Mercklé, Pierre; Zalc, Claire
The paper's main objective is to reflect, from both a sociological and a historiographical perspective, on how to use and how to teach quantitative methods in the social sciences. French and American social scientists, whether apprentices or confirmed, often encounter during their work a crucial need to use quantitative methods. But which methods do each favor? And how to teach these methods? In strongly varying national and disciplinary contexts, what are the directions taken by the revival of interest for quantitative methods? Comparing current pedagogical practices may be a heuristic way to raise crucial questions about historiographical uses of quantitative methods, and give way to a cautious advocacy of reflective uses of quantitative methods in the social sciences.